2018
DOI: 10.1007/s10571-018-0579-4
|View full text |Cite
|
Sign up to set email alerts
|

Continued Tumor Reduction of Metastatic Pheochromocytoma/Paraganglioma Harboring Succinate Dehydrogenase Subunit B Mutations with Cyclical Chemotherapy

Abstract: Patients harboring germline mutations in the succinate dehydrogenase complex subunit B (SDHB) gene present with pheochromocytomas and paragangliomas (PPGL) that are more likely malignant and clinically aggressive. The combination chemotherapy cyclophosphamide, vincristine, and dacarbazine (CVD) was retrospectively evaluated in patients with SDHB-associated metastatic PPGL.Query Twelve metastatic PPGL patients harboring SDHB mutations/polymorphisms with undetectable SDHB immunostaining were treated with CVD. CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…154 Very recently Jawed et al studied 12 patients with a metastatic PGL/PCC, all with SDHB mutation, who received CVD; a marked efficacy was noted. 155 Two out of 12 patients had a complete remission and eight patients a partial response. The median duration of response was 478 days, with a median progression-free survival of 930 days.…”
Section: Heat Shock Protein 90 Inhibitorsmentioning
confidence: 93%
See 1 more Smart Citation
“…154 Very recently Jawed et al studied 12 patients with a metastatic PGL/PCC, all with SDHB mutation, who received CVD; a marked efficacy was noted. 155 Two out of 12 patients had a complete remission and eight patients a partial response. The median duration of response was 478 days, with a median progression-free survival of 930 days.…”
Section: Heat Shock Protein 90 Inhibitorsmentioning
confidence: 93%
“…Both patients showed hypermethylation of the MGMT promotor region, suggesting that monotherapy of temozolomide may benefit patients with metastatic SDHB‐ related PGL/PCC . Very recently Jawed et al studied 12 patients with a metastatic PGL/PCC, all with SDHB mutation, who received CVD; a marked efficacy was noted . Two out of 12 patients had a complete remission and eight patients a partial response.…”
Section: Implications For Treatment Of Metastatic Pgl/pccmentioning
confidence: 99%
“…A meta-analysis involving 50 MPP patients showed that the effective rate of CVD, in terms of tumor volume, was 55% (7). A recent retrospective study showed that, in 12 MPP patients with SDHB gene mutation, all patients had tumor reduction (12-100% by RECIST) upon CVD (6), which suggests CVD therapy probably works better in patients with SDHB mutation. However, CVD is not effective in all patients with SDHB mutation (patient 1 and patient 2 in Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular targeted therapy, such as sunitinib, has shown great potential in the treatment of MPP, but needs to be further investigated (4). Chemotherapy mainly includes CVD regimen (cyclophosphamide, vincristine, and dacarbazine) and temozolomide (TMZ) (5,6). CVD is the most commonly used chemotherapeutic regimen for MPP (7), and TMZ, an oral alkylation chemotherapeutic agent, was first reported to be used for the treatment of MPP in 2006 (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to I-131-MIBG therapy, peptide receptor radionuclide therapy had logistic and radiation-safety advantages [43] . As for the chemotherapy, the combination chemotherapy cyclophosphamide, vincristine, and dacarbazine (CVD) was recommended to be considered part of the initial management in patients with metastatic succinate dehydrogenase complex subunit B (SDHB)-related PPGL, because cyclical CVD chemotherapy lead to continued tumor reduction of metastatic PPGL harboring SDHB mutations [44] . Meanwhile, in our results, adjuvant therapy, radiotherapy, and chemotherapy can improve the CSS of the patients with PPGL.…”
Section: Discussionmentioning
confidence: 99%